Sari Buah Stroberi (Fragaria vesca I.), Sari Buah Tomat (Solanum lycopersicum), dan Kombinasi antara Kedua Sari Buah untuk Meningkatkan Kualitas Spermatozoa Mencit yang Terpapar Asap Rokok Elektrik - Ainuris Zakiyah; Sukarjati Sukarjati; Vivin Andriani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
In Indonesia, there is a tendency to increase the use of e-cigarettes. The content of e-cigarettes can increase Reactive Oxygen Species (ROS) thereby reducing the quality of spermatozoa. This research is an experimental study using a completely randomized design which aims todetermine the potential of strawberry juice, Tomato juice and the combination of the two juices at several concentrations on the sperm quality of mice exposed to e-cigarette smoke. The experimental animals were 48 male mice aged 3 months and weighing 27 g - 30 g. E-cigarette smoke exposed to mice using a vaporizer containing e-liquid with a nicotine content of 3 mg as much as 1.5 ml was exposed for 10 minutes a day for 36 days. The concentrations of strawberry, Tomato juice and the combination of the two juices used were 50%, 75% and 100%. The motility, viability and morphology of sperm were observed using a microscope. Data were analyzed by one-way ANOVA and LSD. The results showed that there was an effect of strawberry, Tomato juice and both combinations of fruit juice on motility (p=0.000), viability (p=0.000) and morphology (P=0.000). The fruit juice that has the most potential to improve the sperm quality of mice due to exposure to e-cigarette smoke is a combination of strawberry: Tomato juice with a concentration of 100:100. The conclusion of this study is that the combination of strawberry and Tomato juice can be used as an increase in sperm quality due to exposure to e-cigarette smoke.